Paraganglioma and pheochromocytoma upon maternal transmission of SDHD mutations - Bayley, Jean-Pierre (BMC Med Genet, 2014)
BACKGROUND: The SDHD gene encodes a subunit of the mitochondrial tricarboxylic acid cycle enzyme and tumor suppressor, succinate dehydrogenase. Mutations in this gene show a remarkable pattern of parent-of-origin related tumorigenesis, with almost all SDHD-related cases of head and neck paragangliomas and pheochromocytomas attributable to paternally-transmitted mutations. METHODS: Here we explore the underlying molecular basis of three cases of paraganglioma or pheochromocytoma that came to our attention due to apparent maternal transmission of an SDHD mutation. We used DNA analysis of family members to establish the mode of inheritance of each mutation. Genetic and immunohistochemical studies of available tumors were then carried out to confirm SDHD-related tumorigenesis. RESULTS: We found convincing genetic and immunohistochemical evidence for the maternally-related occurrence of a case of pheochromocytoma, and suggestive evidence in a case of jugular paraganglioma. The third case appears to be a phenocopy, a sporadic paraganglioma in an SDHD mutation carrier with no immunohistochemical or DNA evidence to support a causal link between the mutation and the tumor. Microsatellite analysis in the tumor of patient 1 provided evidence for somatic recombination and loss of the paternal region of chromosome 11 including SDHD and the maternal chromosome including the centromere and the p arm. CONCLUSIONS: Transmission of SDHD mutations via the maternal line can, in rare cases, result in tumorigenesis. Despite this finding, the overwhelming majority of carriers of maternally-transmitted mutations will remain tumor-free throughout life.